Modular synthesis of new C-aryl-nucleosides and their anti-CML activity. Issue 10 (1st June 2018) - Marzag, Hamid; Zerhouni, Marwa; Tachallait, Hamza; Demange, Luc; Robert, Guillaume; Bougrin, Khalid; Auberger, Patrick; Benhida, Rachid
Graphical abstract: Abstract: The C -aryl-ribosyles are of utmost interest for the development of antiviral and anticancer agents. Even if several synthetic pathways have been disclosed for the preparation of these nucleosides, a direct, few steps and modular approaches are still lacking. In line with our previous efforts, we report herein a one step - eco-friendly β-ribosylation of aryles and heteroaryles through a direct Friedel-Craft ribosylation mediated by bismuth triflate, Bi(OTf)3 . The resulting carbohydrates have been functionalized by cross-coupling reactions, leading to a series of new C -aryl-nucleosides (32 compounds). Among them, we observed that 5d exerts promising anti-proliferative effects against two human Chronic Myeloid Leukemia (CML) cell lines, both sensitive (K562-S) or resistant (K562-R) to imatinib, the "gold standard of care" used in this pathology. Moreover, we demonstrated that 5d kills CML cells by a non-conventional mechanism of cell death.